The darwin affair eaudiobook A novel. - Mason, Tim (HighBridge Audio, 2019)
London, June 1860: When an assassination attempt is made on Queen Victoria, and a petty thief is gruesomely murdered moments later-and only a block away-Chief Detective Inspector Charles Field quickly surmises that these crimes are connected to an even more sinister plot. Was Victoria really the assassin's target? Are those closest to the Crown hiding something? And who is this shadowy figure witnesses describe as having lifeless, coal-black eyes? Soon, Field's investigation exposes a shocking conspiracy in which the publication of Charles Darwin's On the Origin of Species sets off a string of murders, arson, kidnapping, and the pursuit of a diabolical madman named the Chorister. As the investigation takes Field from the dangerous alleyways of London to the hallowed halls of Oxford, the list of possible conspirators grows as the body count escalates. And as he edges closer to the Chorister, he uncovers dark secrets that were meant to remain forever hidden. With ingenuity, intelligence, and wit, debut novelist Tim Mason has created a powerfully entertaining thriller. For fans of Caleb Carr and Carlos Ruiz Zafon, The Darwin Affair is a rousing tale that both Charles Dickens and Sir Arthur Conan Doyle would relish and envy.